An analysis of employment participation and its determinants among older adults in Jambi Province, Indonesia - Riani, Eva; Wijayanto, Arie Wahyu; Rivai, Arham (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
The older adult population in Jambi Province constituted 10.23% of the total population in 2023, categorizing it as an